The Effect of Variation of Drilling Machine Rotation Type KB 20 S On ST-40 Material - Ratlalan, Roberth M. (Jurnal Sains dan Teknik Terapan, 2025)
Drilling is a process of making holes by pressing a rotating chisel on the workpiece. The machining process occurs interaction between the drill bit and the workpiece where the workpiece is cut while the drill bit experiences friction. RPM variations are needed to adjust the drilling to the material being drilled, the size of the drill bit, and the purpose of drilling. testing variations in engine speed against drilling time, using an ST 40 iron workpiece measuring 40x150x8 mm, with the same load weighing 1.9 kg, using a 12 mm diameter drill bit. drilling results the faster the engine speed (rpm) will produce a faster drilling process time, but the resulting threaded hole is not good because the engine speed does not match the drill bit. While the drilling results the slower the engine speed (rpm) will produce a slow drilling process time, but the resulting threaded hole is good because the engine speed matches the drill bit used.